ATMPH 2020
DOI: 10.36295/asro.2020.231236
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric assessment of maxillary sinus in cleft lip and palate patients in comparison to normal subjects

Abstract: Background: Maxillary sinus is pyramidal cavity located in the body of maxilla; represent the largest and closest paranasal sinus to oral cavity. Maxillary sinus shape, size and volume affected by any developmental disturbance occur in midfacial area such as cleft lip and palate. The aim of this study is to evaluate maxillary sinus volume in cleft lip/palate patients and compare it to control normal subjects by using Cone Beam Computed Tomography. Material and method: Thirty four Cone Beam Computed Tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…Of these, 5 were included in the review. Hence, 11 articles were ultimately included in the review 10,11,[16][17][18][19][20][21][22][23][24] .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, 5 were included in the review. Hence, 11 articles were ultimately included in the review 10,11,[16][17][18][19][20][21][22][23][24] .…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported smaller MSV in patients with CLP as compared with those in the control group. 10,16,18,19,21,23 In contrast, 3 studies suggested that there was no significant difference in the MSV of patients with CLP compared with that of the controls 11,22,24 (Table 2).…”
Section: Comparison Of the Msv Of The Cleft Group Versus That Of The ...mentioning
confidence: 97%
See 3 more Smart Citations